Revisiting the archaeological investigations of rice domestication in China during 10,000–7,000 BP in a human behavioral context - Pan, Yan (Frontiers in Earth Science, 2023)
In East Asian archaeology, initial domestication and early dispersal of rice has continuously attracted scholarly interests in the recent decade, which generated abundant new materials and revised opinions. This paper starts with a refreshed understanding of domestication concept that emphasizes the dominant role of human behavior in the mutualistic relationship. A thorough review of the approaches to and data of reconstructing the rice story during 10000-7000 BP demonstrates the causally chained changes in phenotype, genotype, and human behavior in establishment of domestication. Future studies will benefit from the revised paradigm of great potential to extract the archaeological information for explaining multiple mechanisms in rice domestication.